Measurement of the Cognitive Domain Using HOTs in Indonesian Class VIII SMP Iskandar Said - Raiza Aulia; Pramesti Pradna Paramita (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The cognitive domain in Bloom's Taxonomy serves as a framework for categorizing educational goals, curriculum and designing assessments. After a journey of fifty years, Bloom was revised by Kratwohl and Anderson to produce (1) remember, (2) understand, (3) apply, (4) analyze, (5) evaluate, and (6) create. This study aims to describe the implementation of measurement through the cognitive domain. This study uses a quantitative approach, because this research approach can describe cognitive learning outcomes into numbers so that it is easy to analyze the data statistically. The subjects in this study were seventh grade students of SMP Iskandar Said Surabaya. The variable in this study is the cognitive domain. The method or technique of data collection is using the question method or in the form of a test. While the instruments used in this research are in the form of tests to measure the ability of the beginning or end of learning, and observations during the learning process. To measure the cognitive domain using a measuring instrument in the form of a multiple choice test. Where from the results of 40 cognitive questions given to seventh grade students of SMP Iskandar Said Surabaya in Indonesian subjects, 7 questions were retained, 18 questions were revised, and 15 questions were discarded.